2012
DOI: 10.1016/j.automatica.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Extended Kalman filtering with stochastic nonlinearities and multiple missing measurements

Abstract: In this paper, the extended Kalman filtering problem is investigated for a class of nonlinear systems with multiple missing measurements over a finite horizon. Both deterministic and stochastic nonlinearities are included in the system model, where the stochastic nonlinearities are described by statistical means that could reflect the multiplicative stochastic disturbances. The phenomenon of measurement missing occurs in a random way and the missing probability for each sensor is governed by an individual rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
201
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 318 publications
(201 citation statements)
references
References 38 publications
0
201
0
Order By: Relevance
“…[8,20,39] (18) helps to achieve a better approximation and estimation performance in the sequel, which will be demonstrated in the simulation.…”
Section: Polynomial Approximation Of Nonlinear Functionsmentioning
confidence: 99%
“…[8,20,39] (18) helps to achieve a better approximation and estimation performance in the sequel, which will be demonstrated in the simulation.…”
Section: Polynomial Approximation Of Nonlinear Functionsmentioning
confidence: 99%
“…The filtering problems for networked systems with stochastic nonlinearities have already stirred some research interests and some latest results can be found in [16], [43], [45], [52], [101] based on several analysis techniques. For example, by using the Riccati-like difference equation approach, the extended Kalman filter has been designed in [16] for a class of time-varying networked systems with stochastic nonlinearities and multiple missing measurements.…”
Section: B Nonlinear Networked Systemsmentioning
confidence: 99%
“…The filtering problems for networked systems with stochastic nonlinearities have already stirred some research interests and some latest results can be found in [16], [43], [45], [52], [101] based on several analysis techniques. For example, by using the Riccati-like difference equation approach, the extended Kalman filter has been designed in [16] for a class of time-varying networked systems with stochastic nonlinearities and multiple missing measurements. Moreover, the locally optimal Kalman-like filtering algorithms have been developed in [52], [101] for time-varying networked systems with stochastic nonlinearities, where the compensation schemes have been proposed to attenuate the effects from random sensor delays, random parameter matrices and gain-constraints onto the filtering performance.…”
Section: B Nonlinear Networked Systemsmentioning
confidence: 99%
See 2 more Smart Citations